Identification of Synthetic Cannabinoid 5F-ADB (5F-MDMB-PINACA) and Its Metabolite in Urine Sample Using Liquid Chromatography – High Resolution Mass Spectrometer (LC-HRMS) - Rieska Dwi Widayati; Tanti Tanti; Erlana Nindya Maulida; Martin Luther Silubun (Chemistry Department, The University of Brawijaya, 2020)
Synthetic cannabinoids are commonly known as Gorillas Tobacco, Hanomans Tobacco or Ganeshas Tobacco in Indonesia. Those products are camouflaged as a tobacco related to the number of smokers in Indonesia. The 5F-ADB (5F-MDMB-PINACA) has become an issue since 2016. It was undetectable by conventional drug testing methodology such as immunoassay method. GC-MS as a routine method analysis is not recommended also for detecting the metabolites from biological specimen with low concentration. The paper report LC-HRMS based method for identification of 5F-ADB and its metabolites in urine sample. Various of volume injections (1, 3, and 6 µL) was studied. Sample was acidified with concentrate of HCl, then undergo extraction with EXtrelut® Column NT3 prior to LC-HRMS analysis. The full method was operated for MS/dd-MS2 identification. The 5F-ADB and its ester hydrolysis metabolite, 5F-ADB metabolite 7 (C19H27FN3O3+) was detected in urine sample.